Kindler syndrome with intractable squamous cell carcinoma arising in the oral cavity: A case report and review of cases - Sugauchi, Akinari; Uchihashi, Toshihiro; Isomura, Emiko Tanaka; Seki, Soju; Kimura, Yuka; Kiyohara, Eiji; Fujimoto, Manabu; Tanaka, Susumu; Tanemura, Atsushi (Current problems in cancer. Case reports, 2025)
Kindler syndrome (KS) is an extremely rare subtype of epidermolysis bullosa characterized by blistering of the extremities, progressive polymorphous skin atrophy, and mucosal inflammation. There is no curative therapy for KS, only symptomatic treatment. Patients with KS generally present with squamous cell carcinoma of the extremities and lips, which are more susceptible to irritation, with only a few cases involving the oral cavity. Herein, we report the case of a 53-year-old female patient with KS, who developed oral squamous cell carcinoma. While initial treatment with intensity-modulated radiation therapy was successful, shortly thereafter, she relapsed and was not responsive to multiple rounds of chemotherapy. Ultimately, palliative care at home was suggested. While the patient received radiation therapy and chemotherapy, she complained of difficulty breathing due to the tumor, especially during the last round of chemotherapy. As a result of aggressive weight reduction of tumor necrotic tissue, the patient's respiratory distress improved. Based on our experience in this case, we propose that the removal of oral tumor necrotic tissues, which is not often performed as part of conventional curative treatment approaches, can sometimes be efficacious for the maintenance of the quality of life, especially in a palliative context for OSCC patients with KS.